Social determinants of health and patient outcomes in Long-term Acute Care Hospitals: A scoping review - Christian M. Noval; Katherine Brooks; Leila Ledbetter; Erin Simon; Sharron Rushton; Donald E. Bailey Jr (PLoS ONE, 2026)
Introduction Long-term acute care hospitals (LTACHs) are certified acute care facilities specifically designed to provide continuous specialized care and extended recovery for patients with chronic critical illness. LTACHs have high mortality rates because patients with complex care needs often experience fluctuations in their recovery trajectory; however, these outcomes are not solely driven by medically related factors. Social determinants of health (SDoH) contribute to up to 55% of all health outcomes; therefore, understanding how characteristics of SDoH influence patterns of health care utilization and health outcomes among patients in LTACH setting is crucial for optimizing outcomes in this population. Methods and materials This scoping review utilized the U.S. Department of Health and Human Services Healthy People 2030 SDoH framework to describe how SDoH influence outcomes for patients admitted to and discharged from LTACHs. The review covers the literature from 1982 to 2025 across four databases. The Joanna Briggs Institute (JBI) Manual for Evidence Synthesis guided the review and the PRISMA extension for scoping reviews guided the manuscript development. Results Five studies met the inclusion criteria. Findings indicate that the current literature focused on SDoH within the LTACH setting has predominantly concentrated on only three of the five established domains: social and community context, economic context, and healthcare access and quality. Race was identified as a key demographic variable in three studies that examined its association with outcomes such as mortality, morbidity, readmission rates, and health care costs. LTACH location and insurance coverage represented health care access and quality, and income reflected the broader economic context. Conclusion There is limited literature on this topic, and the review findings were insufficient to describe the complex interplay between SDoH variables and key patient outcomes. The degree to which the variables under each SDoH domain have been studied may not provide sufficient information to represent them. Comprehensive research on the effects of SDoH on outcomes of patients in the LTACH setting is warranted to explicate possibly complex causal relationships, inform targeted interventions to improve patient outcomes, and maximize the value of LTACHs, especially in light of the recent facility closures.